Microplastics removal mechanisms in constructed wetlands and their impacts on nutrient (nitrogen, phosphorus and carbon) removal: A critical review - Zhang, Shaochen; Shen, Cheng; Zhang, Fuhao; Wei, Kejun; Shan, Shengdao; Zhao, Yaqian; Man, Yu Bon; Wong, Ming Hung; Zhang, Jin (The Science of the total environment, 2024)
Microplastics (MPs) are now prevalent in aquatic ecosystems, prompting the use of constructed wetlands (CWs) for remediation. However, the interaction between MPs and CWs, including removal efficiency, mechanisms, and impacts, remains a subject requiring significant investigation. This review investigates the removal of MPs in CWs and assesses their impact on the removal of carbon, nitrogen, and phosphorus. The analysis identifies crucial factors influencing the removal of MPs, with substrate particle size and CWs structure playing key roles. The review highlights substrate retention as the primary mechanism for MP removal. MPs hinder plant nitrogen uptake, microbial growth, community composition, and nitrogen-related enzymes, reducing nitrogen removal in CWs. For phosphorus and carbon removal, adverse effects of MPs on phosphorus elimination are observed, while their impact on carbon removal is minimal. Further research is needed to understand their influence fully. In summary, CWs are a promising option for treating MPs-contaminated wastewater, but the intricate relationship between MPs and CWs necessitates ongoing research to comprehend their dynamics and potential consequences. [Display omitted] •CWs efficiently remove MPs, with most achieving >90 % efficiency.•Substrate size and CW design are key factors in MPs removal by CWs.•Substrate retention is the dominant mechanism of MPs' removal in CWs.•MPs hinder plant N uptake, alter microbe communities, and reduce N removal in CWs.•MPs affect phosphorus removal, less impact on carbon removal in CWs.